Melatonin alleviates arsenic (As) toxicity in rice plants via modulating antioxidant defense system and secondary metabolites and reducing oxidative stress. (1st February 2023) - Jan, Rahmatullah; Asif, Saleem; Asaf, Sajjad; Lubna,; Du, Xiao-Xuan; Park, Jae-Ryoung; Nari, Kim; Bhatta, Dibya; Lee, In-jung; Kim, Kyung-Min
Abstract: The Arsenic (As) load on the environment has increased immensely due to large-scale industrial and agricultural uses of As in several synthetic products, such as fertilizers, herbicides, and pesticides. Melatonin is a plant hormone that has a key role in abiotic stress inhibition, but the mechanism of resilience to As stress remains unexplored in rice plants. In this study, we determined how As affects rice plant and how melatonin facilitate As stress tolerance in rice. Here we investigated that, exogenous melatonin reduced As stress by inducing anthocyanin biosynthesis. Melatonin induced the expression of anthocyanin biosynthesis genes such as PAL, CHS, CHI, F 3 H, DFR, and ANS, which resulted in 1659% and 389% increases in cyanidin and delphinidin, respectively. Similarly, melatonin application significantly induced SA and ABA accumulation in response to As stress in rice plant. Application of melatonin also significantly reduced expression of PT-2 and PT-8 (transporter genes) and reduced uptake of As and its translocation to other compartments. Melatonin and As analysis revealed that melatonin application significantly reduced As contents in the melatonin-supplemented plants, suggesting that As uptake is largely dependent on either the melatonin basal level or anthocyanin in rice plants. In this study, we investigated new symptoms on leaves, which can severely damage leaves and impair photosynthesis. However, anthocyanin as a chelating agent, detoxifies As in vacuole and reduces oxidative stress induced by As. Graphical abstract: Image 1 Highlights: Arsenic causes severe oxidative stress in rice and affects rice grain quality and quantity. Melatonin inhibits As uptake and translocation by reducing the expression of transporter genes. Melatonin increases anthocyanin biosynthesis in rice plants by inducing biosynthesis-related genes. Stress tolerance is mostly dependent on anthocyanin basal levels in rice plants. Melatonin induces phytohormonal regulation in response to As stress in rice plants.